Variability in the Structure of Phytoplankton Assemblages in relation to Human Disturbance in Southern Coast of Tunisia. (24th June 2014) - Mabrouk, Lotfi; Dammak, Lamia; Hamza, Asma; Mahfoudhi, Mabrouka; Bradai, Med-Najmeddine
Abstract : We investigated the impact of industrial effluents on phytoplankton assemblage in southern Tunisia (Skhira). We specifically addressed changes in microalgae composition caused by this anthropogenic interference. A hierarchical sampling design was used to compare planktonic microalgae structure between one disturbed station and one control station. Samples were collected by scuba diving at 5 m depth in August 2012. A total of 76 microalgae taxa were identified. Dinoflagellates abundance was low in the disturbed station, especially Gonyaulacales and Prorocentrales due to P-limitation, whereas diatoms and cyanobacteria abundance were low in control station which is characterized by Si-limitation.